The dynamics of macroeconomics variables and the volatility of Indonesia stock markets: evidence from Islamic and conventional stock markets - Abduh, Muhamad; Surur, Miftaskhus (International Association of Islamic Banks, 2013)
This study aims to investigate the impact of the movement of macroeconomic variables upon the Indonesia stock markets, both Islamic and conventional stock markets, by using vector error correction model. The macroeconomic variables employed in the study are exchange rate, economic growth, and inflation within the period of January 2003 to December 2010. The result shows that in the long run, the performance of the stock markets is negatively influenced by exchange rate and positively influenced by industrial production index. Interestingly, inflation is found to be significant only for conventional stock markets with negative relationship.